Monogenoideos en piel y branquias de calíctidos (siluriformes: callychthyidae) adquiridos en centros de acopio de la ciudad de Iquitos, Loreto-Perú - García Panduro, Jusimara (2024)
Fish of the Callychthyidae family are of great commercial importance in the Peruvian Amazon, since their species are exported to different countries around the world. These fish, kept in captivity, can present infestations caused by monogenoids in skin and/or gills. Given the need to know the monogenoids that parasitize commercially important callitrichids, the main objective of this study was the taxonomic identification at species level of the monogenoids present in the skin and gills of callitrichids (Siluriformes: Callychthyidae). The study was conducted from January to June 2023, through the observation, search and identification of ectoparasites in thirteen species of Callitrichids (20 individuals per fish) corresponding to: Brochis splendens, B. multiradiatus, B. virginiae, B. ambiacus, B. agassizii B. reticulatus, B. arcuatus, B. leopardus, Hoplisoma panda, H. trilineatus, H. weitzmani, Osteogaster aeneus and, O. rabauti, acquired in two collection centers in the city of Iquitos. The first collection center was the Jumper Cat Collection Center, located in the district of Belén, and the second was the Acuacorp Collection Center, located in the town of Rumo Cocha, district of San Juan Bautista. The acquired fish were processed and analyzed at the Parasitology and Aquaculture Health Laboratory of the Peruvian Amazon Research Institute (IIAP) in Iquitos, Loreto-Peru. The samples were analyzed with the aid of a stereoscope and then mounted on permanent slides with Hoyer clarifying medium and stained with Gomori's Trichrome. The slides were observed under an optical microscope and the identification was carried out using books, taxonomic articles and original works. The results of the study allowed the taxonomic identification of 15 species of Monogenoidea within which six species and three morphospecies of the genus Philocorydoras were found in gills. Six morphospecies of the genus Gyrodactylus were reported in skin samples. The results allow us to conclude that complementary taxonomic studies are necessary in order to formally describe the morphospecies reported in this study, as well as to continue studies on other Callitrichid species in the Peruvian Amazon.